The 'Eigenständig werden' prevention trial: a cluster randomised controlled study on a school-based life skills programme to prevent substance use onset. Issue 2 (1st November 2011) - Hansen, Julia; Hanewinkel, Reiner; Maruska, Karin; Isensee, Barbara
Abstract : Objective: To implement and evaluate 'Eigenständig werden 5+6' ('Becoming Independent 5+6'), a school-based curriculum for grades 5 and 6 developed on the basis of evidence-based criteria for effective drug prevention curricula in schools. Evaluation of the programme includes efficacy, feasibility and practicability in daily school routine. Methods and results: The intervention 'Eigenständig werden 5+6' consists of 14 teaching units evenly distributed over grades 5 and 6 which are interactively delivered, and a parent component. Programme effects are studied in a four wave cluster randomised controlled trial with two arms, an intervention and a control group. Self-completed questionnaires from students and teachers are collected by trained research staff. 45 schools, 172 classes and 3444 students with a mean age of 10.37 years (SD=0.59) and 47.9% girls from four federal states in Germany were assessed at baseline. 1685 students in 81 classes were assigned to intervention classes, 1759 students in 91 classes to the control arm. No differences between conditions were found for age, gender, immigration background, socioeconomic status, substance use or life skills at baseline. Exceptions were higher self-efficacy (t(3438)=2.34, p=0.02, d=0.08) and empathy (t(3302)=2.4, p=0.02, d=0.09) in the control group, whereas class climate seemed better in the intervention group (t(3037)=2.01, p=0.05, d=0.07), but effect sizes state marginal differences. Conclusion: Baseline data suggest that the initial conditions are favourable for testing programme efficacy since distribution of baseline levels of the outcomes did not differ in the intervention and control groups, except for negligible differences between self-efficacy and empathy, which were higher in the control group, and class climate, which was higher in the intervention group. Trial registration number: Current Controlled Trials ISRCTN99442407 .